Evaluating service quality and tourists' satisfaction of spa facilities : a case of Gadek Hot Spring [electronic resource] - Hadi Ganjalikhan Hakemi, 1983- (2013)
Thesis (Sarjana Sains (Perancangan Pelancongan)) - Universiti Teknologi Malaysia, 2013